PENGEMBANGAN POTENSI WISATA ALAM SECARA SPASIAL DESA BONGO KECAMATAN BATUDAA PANTAI KABUPATEN GORONTALO (Spatial Natural Tourism Potential Development of Bongo District of Batudaa Pantai Gorontalo Regency) - Titin Umi Rahayu; Ahmad Syamsu Rijal; Ivan Taslim (Universitas Muhammadiyah Gorontalo, 2020)
The purpose of this study is to analyze the development of spatial natural tourism potential and identification of Bongo torism potential using SWOT analysis. By usung a qualitative descriptive method and data source in the from of primary and secondary data. Primary data covering field observation, interview and secondary data covering the map of RBI 1: 25.000, satellite image of Google Maps and data of visitor number which then described by SWOT matrix. The result of this study indicate the Bongo village has good natural tourism potential to be developed, in terms of attractiveness with the hills are very beautiful types of taours that can be developed that is a natural panorama taour and outbound tourism other than that Bongo village has a Dulanga beach with coral reef and other merine biota with a decent tour to be developed that is snorkeling tour. As for supporting facilities and infrastructure of natural attractions Bongo village needs to be added in order to meet the needs of tourist who visit because wih adequate faciliteis and infrastructure can increase the number of tourists both local and foreign.